2011
DOI: 10.1055/s-0031-1283175
|View full text |Cite
|
Sign up to set email alerts
|

Sports Therapy for Attention, Cognitions and Sociality

Abstract: The aim of the present study was to understand if sport improves attention symptoms, social competency, and cognitive functions in children with attention deficit and hyperactivity disorder (ADHD). The present study was designed as a 6-week, prospective trial, including 12 sessions of education/sports therapy. 13 ADHD children participated in a 90-min athletic activity (sports-cADHD) twice a week, while 15 ADHD children received education on behavior control (edu-cADHD). During the 6-week treatment period, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
3
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(143 citation statements)
references
References 36 publications
3
126
3
11
Order By: Relevance
“…35 In this context, Kang et al demonstrated a positive correlation between physical exercise and improved attention and cognitive symptoms. 36 Second, the elements of motion simulation in EAA/T may influence the improvement in ADHD symptoms. The EQUINE-ASSISTED THERAPY FOR CHILDREN WITH ATTENTION-DEFICIT/HYPERACTIVITY DISORDER vestibular system may be stimulated by the child's symmetric and rhythmic body movements while riding a horse.…”
Section: Discussionmentioning
confidence: 99%
“…35 In this context, Kang et al demonstrated a positive correlation between physical exercise and improved attention and cognitive symptoms. 36 Second, the elements of motion simulation in EAA/T may influence the improvement in ADHD symptoms. The EQUINE-ASSISTED THERAPY FOR CHILDREN WITH ATTENTION-DEFICIT/HYPERACTIVITY DISORDER vestibular system may be stimulated by the child's symmetric and rhythmic body movements while riding a horse.…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous randomized controlled trials are necessary to establish causal impacts of regular physical activity on ADHD outcomes. To date, one large and two smaller trials have investigated the impact of multi-week physical activity interventions on children with ADHD (8, 20, 21). Unfortunately, none of these studies reported heart rate, provided sufficient levels of activity to meet current guidelines (53), excluded siblings from analyses (sibling pairs are not independent observations), or met CONSORT criteria for reporting of clinical trials (i.e., blind, randomization, power analysis, allocation concealment, specification of primary outcome), thereby limiting interpretation (36).…”
Section: Introductionmentioning
confidence: 99%
“…However, non-pharmacological behavior modification treatments are also recommended for improving behavioral inhibition deficits and executive dysfunction in ADHD 15. For example, neurofeedback therapy, multimodal psychosocial treatment, school-based programs, working memory training, parent training, and self-monitoring have been introduced and applied as alternative treatments 10,16,17,18,19,20. EEG biofeedback, meditation, channel specific perceptual training, and vestibular stimulation have been applied for ADHD as alternative treatment with a promising prospective evidence 20.…”
Section: Introductionmentioning
confidence: 99%